Beverage waste derived biomaterials for tissue engineering. Issue 19 (15th September 2017) - Yates, M.; Ramos-Gomez, M.; Civantos, A.; Ramos, V.; López-Lacomba, J. L.; Sanz Casado, J. V.; Lluis Tarterra, J.; Fité Luis, B.; Martin-Luengo, M. A.
Abstract : For the first time waste from the beverage manufacturing industry has been valorised as an in vivo tissue engineering scaffold. Abstract : The waste material from the beverage manufacturing industry was valorized as a renewable source for the manufacture of biomaterials capable of acting as scaffolds for tissue engineering. Environmentally friendly design of both structural and textural properties produced biomaterials whose in vivo properties were similar to those of a commercial biomaterial.